Amelioration of dextran sulfate sodium-induced colitis by autoinducer-2-deficient Lactiplantibacillus plantarum is mediated by anti-inflammatory effects and alleviation of dysbiosis of the gut microbiota - Qian, Yilin; Ma, Lei; Zeng, Mingyong; Liu, Zunying (Frontiers in Microbiology, 2022)
Lactic acid bacteria (LAB) attenuate dextran sulfate sodium (DSS)-induced colitis in mice by restoring gut flora homeostasis and modulating the immune response. Because synchronous behaviour can be controlled by autoinducer-2 (AI-2)/LuxS-mediated quorum sensing, the Caco-2 cell model and DSS-induced model in C57BL/6 mice were used to explore the unknown effects of these communications involving AI-2 among various intestinal symbiotic species. The results of the cell viability and lactate dehydrogenase leakage assays indicated that the tested strains (the wild-type strains and AI-2-deficient mutants) were characterised by equal cytoprotection from hydrogen peroxide-induced injury independently of AI-2. The results of the assays of multiple indicators and proinflammatory cytokines characteristic for the symptoms of colitis in mice showed that oral administration of AI-2-deficient mutants for 7 d was more effective in ameliorating inflammation than the treatment with the wild-type strains. The treatment with AI-2-deficient mutants enriched potential probiotics (e.g., Lactobacillaceae) and controlled the proliferation of potentially harmful bacteria (e.g., Helicobacteraceae) to achieve the transformation of intestinal flora. These mutants regulated short-chain fatty acids and the intestinal epithelial barrier, thereby promoting the maintenance of relatively favourable intestinal homeostasis. These results demonstrated that the AI-2-deficient mutants provided a more pronounced ameliorative effect on colitis in a mouse model, suggesting that the background of the LAB effect is associated with the alterations in colonic flora induced by AI-2.